(3GdfGSN hGdefShN aj GdbQBfs - (3GdMGaX CHh efUhQs
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg hGdSdGe Ydi YHGOg hHYO agPG cJGH LeYJ ajg LejY eG aj GdbQBf ef GdBjGJ GdfGSNI hGdefShNIs
(3BNQgG (B:s
(3GdYUQ EdG GdPjf BefhG hYedhG GdUGdMGJ GdBjI agPg LedI GdehGVY GdfhGSN hgj eGFI ehVY hehVhYGJ JLeYgG SHY hKdKhf ShQIs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3GdMhGTj h GdJYdjbGJ (B:s
(3JYdjbGJs
Keywords: (3GdJaSjQ hYdhe GdbQBfs